ANALISIS KEAMANAN BROWSER DALAM BERSOSIAL MEDIA MENGGUNAKAN METODE INSTITUTE OF JUSTICE (NIJ) - Zikri Sulthoni Daulay; Rini Indrayani (Djtechno: Jurnal Teknologi Informasi, 2022)
Active users of social media in Indonesia continue to increase every year. But there are still many users who do not understand the security of accessing social media, especially when accessing with a browser. For this reason, the browsers analyzed in this study are the Google Chrome and Mozilla Firefox browsers with two modes, namely public mode and incognito mode. This study aims to identify the level of browser security in using social media in the browser. The method used is the NIJ (National Institute of Justice) methodology. The tool used to get the data is using the FTK Imager 4.5.0.3 application. The results of this study are when accessing social media Facebook, Instagram, Twitter is not safe using Google Chrome and Mozilla Firefox browsers with public mode and incognito mode because user_id, email and some passwords are still detected in the FTK Imager tool. For the percentage results obtained in the study, namely 89% of user_id data, passwords, emails found in public mode Google Chrome browsers, 67% data found in incognito mode Google Chrome browsers, 78% data found in public mode Mozilla Firefox browsers, and 89% of data found in Mozilla Firefox browser incognito mode.Keywords: Live Forensics; Institute of Justice; Browser; Media Sosial; FTK Imager